PENERAPAN MODEL ASESMEN PORTOFOLIO PADA PERKULIAHAN PRAKTIK BATU BETON DI PRODI PENDIDIKAN TEKNIK BANGUNAN JPTS FPTK UPI - Dimastra, Gent (2014)
Portofolio asessment model had been used for concrete practice course which can evaluate study result not only at the end of the given time with focusing on cognitive aspect, a little of psychomotoric, and almost untouched affective aspect but the whole aspect instead. Which hoped can help the lecturer to judge as evaluate conceptual that can be viewed not to exceed or harm the studenst. This research using descriptive qualitative approximation, with indepth interview. Sample in this research is concrete practice course lecturers, its acquaintance and 2013 building engineering of education students. Research subject is five persons. And using purposive sampling as sample withdrawal. From result of the reseach can be assumed that in concrete practice course, portofolio asessment model can be used to see student development graphic and evaluate study result through 3 judgement aspect (cognitive, affective and psychomotoric) on process and product of practice using jobsheet. Judgement taken by criteria and itegrity of competence. However its still have obstacles which include individual judgement caused by practice implementation is as a team due to variety restriction, and product judgement is more precise than process judgement. Because of that lecturers intuition to judge on process and judgement details when filing the archive is very important so the judgement value will be objective.